Efficacy of atorvastatin in prevention of atrial fibrillation after heart valve surgery in the PROFACE trial (PROphylaxis of postoperative atrial Fibrillation After Cardiac surgEry). Issue 3 (28th March 2016) - Carrascal, Yolanda; Arnold, Roman J.; De la Fuente, Luis; Revilla, Ana; Sevilla, Teresa; Arce, Nuria; Laguna, Gregorio; Pareja, Pilar; Blanco, Miriam
Abstract: Background: To evaluate the efficacy of perioperative atorvastatin administration for prophylaxis of postoperative atrial fibrillation (POAF) after heart valve surgery. Methods: Our study included 90 patients with heart valve disease who were scheduled to undergo elective cardiac surgery. Cases with previous AF or preoperative beta‐blocker therapy were excluded. Patients were randomized into the atorvastatin group, which included 47 patients who received 40 mg/day of atorvastatin 7 days before and after the surgery and the control group, which included 43 patients. Primary endpoint was the occurrence of POAF. Secondary endpoints included modifications in the preoperative and postoperative levels of the markers of inflammation (C‐reactive protein [CRP]), myocardial injury (ultrasensitive troponin T and creatinine phosphokinase MB [CPK‐MB]), and cardiac dysfunction (pro‐brain natriuretic peptide [proBNP]) related to POAF and changes in the echocardiographic parameters, such as atrial electromechanical interval, A wave, E/A ratio, and Doppler imaging systolic velocity wave amplitude, related to POAF. Results: No relationship between atorvastatin administration and reduction in the incidence of POAF was observed (42.6% in the atorvastatin vs. 30.2% in the control group) (p=0.226). No difference in the levels of CPK‐MB, ultrasensitive troponin T, CRP, or proBNP and in the analyzed echocardiographic parameter was detected between both groups. Conclusions: Atorvastatin in the described dose, was not adequate for the prophylaxis of POAF after heart valve surgery. It was ineffective in controlling the inflammatory phenomena, myocardial injury, and echocardiographic predictors of POAF.